2011
DOI: 10.1080/13674670903485629
|View full text |Cite
|
Sign up to set email alerts
|

Religion, ethnicity, coping style, and self-reported self-harm in a diverse non-clinical UK population

Abstract: Previous studies of ethnic and cultural differences in self-harm have focussed on overdose and suicide attempts by South Asian women. Research comparing ethnic groups has rarely examined religion or nationality. To achieve a more balanced approach this study examined self-harm methods and self-injury across gender, religion and ethnic group in a non-clinical population. Six hundred and seventeen university students completed a questionnaire asking whether they had ever harmed themselves, and the frequency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
4
30
1
Order By: Relevance
“…African Americans and Hispanics tended to used more emotion-focused coping, such as distancing and accepting responsibility than Whites. Contrary to these findings and the aforementioned theory, Borrill, Fox, and Roger (2011) found that among a sample of UK students who often engaged in self-harming activities (e.g., cutting),…”
Section: Intersections Among Ses Race and Ethnicitycontrasting
confidence: 84%
“…African Americans and Hispanics tended to used more emotion-focused coping, such as distancing and accepting responsibility than Whites. Contrary to these findings and the aforementioned theory, Borrill, Fox, and Roger (2011) found that among a sample of UK students who often engaged in self-harming activities (e.g., cutting),…”
Section: Intersections Among Ses Race and Ethnicitycontrasting
confidence: 84%
“…In contrast, Borrill et al (2011) found rates for self-harm were low among Hindu and Sikh university students in the United Kingdom.…”
Section: (V) Suicidementioning
confidence: 64%
“…A recent study of self-harm among university students found rates significantly higher among Asian females than males, though Asian rates overall were unremarkable (Borrill, Fox, & Roger, 2011). Evidence from India suggests mental illness may be implicated relatively rarely, and social and situational stresses (work, financial and alcohol problems for men, domestic problems, inlaw relationships and victimisation for women) are relatively common compared to evidence from Europe and North America (Parkar, Dawani, & Weiss, 2008).…”
Section: (V) Suicidementioning
confidence: 97%
“…In a qualitative study (Wagner & Rehfuss, ), participants who self‐injure reported that they were negatively influenced by a Christian upbringing, but exploration and development of personal spiritual and religious beliefs and practices had positive effects on reducing the occurrence of participants' self‐injury rates. Borrill, Fox, and Roger () found that individuals who endorsed a religion (i.e., Christian, Muslim, Hindu) were less likely to report repeated NSSI than individuals who did not endorse a religion. Consistent with this finding, Klonsky and Glenn () found that individuals who self‐injure reported that the use of spiritual and religious coping mechanisms helped them to resist urges to self‐injure.…”
Section: Spirituality/religiosity As a Protective Factor Against Nssimentioning
confidence: 99%